2017
DOI: 10.1161/circulationaha.117.028351
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of EIF2AK4 Mutation Carriers in a Large Cohort of Patients Diagnosed Clinically With Pulmonary Arterial Hypertension

Abstract: BACKGROUND:Pulmonary arterial hypertension (PAH) is a rare disease with an emerging genetic basis. Heterozygous mutations in the gene encoding the bone morphogenetic protein receptor type 2 (BMPR2) are the commonest genetic cause of PAH, whereas biallelic mutations in the eukaryotic translation initiation factor 2 alpha kinase 4 gene (EIF2AK4) are described in pulmonary veno-occlusive disease/pulmonary capillary hemangiomatosis. Here, we determine the frequency of these mutations and define the genotype-phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
101
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 38 publications
7
101
1
4
Order By: Relevance
“…Our study found that GCN2 governs important nutritional responses and, if dysfunctional, leads to altered whole body metabolism. It is tempting to speculate that as a result of this altered metabolism subjects bearing deleterious mutations in Gcn2 (EIF2AK4) gene have higher chances of developing metabolic conditions later in life such as pulmonary arterial hypertension (46). This work provides a foundation for personalized approaches in usage of other GCN2-activating drugs as well as dietary approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that GCN2 governs important nutritional responses and, if dysfunctional, leads to altered whole body metabolism. It is tempting to speculate that as a result of this altered metabolism subjects bearing deleterious mutations in Gcn2 (EIF2AK4) gene have higher chances of developing metabolic conditions later in life such as pulmonary arterial hypertension (46). This work provides a foundation for personalized approaches in usage of other GCN2-activating drugs as well as dietary approaches.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, PAH patients have been reported to carry multiple gene mutations in at least two distinct pathogenic loci [36,37], furthering the hypothesis that these multiple hits may originate from the complex genetic inheritance of several mutations. Our findings of convergent, miR-130/301-specific actions of seemingly disparate factors relevant to hereditary PAH now offer new insights into this multiple-hit hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hadinnapola et al [16] performed whole genome sequencing in 808 patients with IPAH, 56 with hPAH and 16 patients with PVOD/PCH. Bi-allelic mutations of EIF2AK4 were identified in 5 PVOD/PCH patients and in 9 IPAH patients (1%).…”
Section: Genetic Alterations In Pvod/pchmentioning
confidence: 99%
“…Bi-allelic mutations of EIF2AK4 were identified in 5 PVOD/PCH patients and in 9 IPAH patients (1%). Interestingly, EIF2AK4 positive IPAH patients, investigated both by Best et al [15] and by Hadinnapola et al [16], exhibited clinical symptoms that might be indicative of PVOD/PCH.…”
Section: Genetic Alterations In Pvod/pchmentioning
confidence: 99%